Polymetallic Complexes, Part LXI: Complexes of Co(II), Ni(II), Cu(II), Zn(II), Cd(II) and Hg(II) withand Donor Tridentate Ligands - B. Mahapatra, Bipin; Raval, M.K.; K. Behera, Ajaya (Asian Journal of Chemistry, 2010)
Twelve metal complexes of Co(II), Ni(II), Cu(II), Zn(II), Cd(II) and Hg(II) with tridentate donor ligand, N-[phenacyl(phenylmethyl)]-anthranilic acid and donor tridentate ligand, 2-carboxy[phenyl-phenacyl(phenylmethyl)]ether have been synthesized. The complexes of first two metal ions are suggested to be octahedral and the complexes with rest are tetrahedral in configuration. The characterisation of the complexes is made basing upon analytical, conductance, magnetic susceptibility measurement, IR, electronic and ESR spectral data. All the complexes are dimeric in nature, the dimerisation is achieved through the bidentate carboxylate group.